2018
DOI: 10.1016/j.heliyon.2018.e00757
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-epidemiological investigation on Varicella Zoster Virus indicates multiple clade circulation in Maharashtra state, India

Abstract: BackgroundVaricella Zoster Virus (VZV) is consistently in circulation and shows an increase in disease burden during the spring season. Due to a wide range of clinical presentation from a vesicular rash to bleeding or neurological complications, it makes the clinical diagnosis difficult. The present study aims to understand whether the same strain of virus is responsible for the increase in the seasonal outbreaks occurring in different parts of the country with reference to the samples from Maharashtra, Rajast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Previously chickenpox was noted as children's disease as only 2 % adults affected by this disease 8 . But further it was observed equally in adults too 9,10 . In our study also 39.47 % (45/114) positive patients were more than 15 years.…”
Section: Discussionmentioning
confidence: 84%
“…Previously chickenpox was noted as children's disease as only 2 % adults affected by this disease 8 . But further it was observed equally in adults too 9,10 . In our study also 39.47 % (45/114) positive patients were more than 15 years.…”
Section: Discussionmentioning
confidence: 84%
“…The study conducted by Rima et al. revealed the circulation of multiple clades (1/3 and 4/5) of VZV in three Indian states [ 20 ]. A clinico epidemiological investigation undertaken in the Indian state of Maharashtra revealed mixed clade circulation and the existence of VZV clade 1 in India.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 A similar epidemiological study done in Maharashtra state shows vesicular rash with fever was a common clinical presentation with 82% cases having contact history with VZV positive cases, suggesting higher secondary attack rate. 13 A study assessing the rising trends of chicken pox outbreaks among school children in Kashmir showed a hundred percent of outbreaks occurred in rural areas and there were no difference in occurrence among genders. A seasonal pattern was observed, with cases increasing during warm months.…”
Section: Introductionmentioning
confidence: 99%
“…The findings was similar to study conducted by Sahay et al among chickenpox patients in an infectious disease hospital in Mumbai showed that out of 50 cases, one patient had a history of type 2 diabetes mellitus and tuberculosis. No other immunocompromised conditions were noted 22. …”
mentioning
confidence: 99%